On the Matter of Prepositions: Peter de Bona's The Discourse of the Sublime - Fran Bartkowski (Studies in 20th & 21st Century Literature, 1993)
Review Essay. On the Matter of Prepositions: Peter de Bona's The Discourse of the Sublime
Keywords: On the Matter of Prepositions; preposition; Peter de Bona; The Discourse of the Sublime